Dual Interactions of the Translational Repressor Paip2 with Poly(A) Binding Protein - Khaleghpour, Kianoush (American Society for Microbiology, 2001)
The cap structure and the poly(A) tail of eukaryotic mRNAs act synergistically to enhance translation. This effect is mediated by a direct interaction of eukaryotic initiation factor 4G and poly(A) binding protein (PABP), which brings about circularization of the mRNA. Of the two recently identified PABP-interacting proteins, one, Paip1, stimulates translation, and the other, Paip2, which competes with Paip1 for binding to PABP, represses translation. Here we studied the Paip2-PABP interaction. Biacore data and far-Western analysis revealed that Paip2 contains two binding sites for PABP, one encompassing a 16-amino-acid stretch located in the C terminus and a second encompassing a larger central region. PABP also contains two binding regions for Paip2, one located in the RNA recognition motif (RRM) region and the other in the carboxy-terminal region. A two-to-one stoichiometry for binding of Paip2 to PABP with two independent K(d)s of 0.66 and 74 nM was determined. Thus, our data demonstrate that PABP and Paip2 could form a trimeric complex containing one PABP molecule and two Paip2 molecules. Significantly, only the central Paip2 fragment, which binds with high affinity to the PABP RRM region, inhibits PABP binding to poly(A) RNA and translation.